2020
DOI: 10.1016/j.aquatox.2020.105449
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle progression arrest and modification of cell morphology (shape and biovolume) in the alga Pseudokirchneriella subcapitata exposed to metolachlor

Abstract: Metolachlor (MET) is an herbicide widely used and frequently found (at μg L −1) in aquatic systems. This work aimed to study the modes of action of MET on the green microalga Pseudokirchneriella subcapitata. Algae exposed to 115 or 235 μg L −1 MET, for 48 or 72 h, presented a reduction of metabolic activity, chlorophyll a and b content and photosynthetic efficiency. The exposure to 115 or 235 μg L −1 MET also induced growth yield reduction, mean cell biovolume increase and alteration of the typical algae shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Cell cycle analysis to study the ploidy of the cultures revealed that WT cultures had a higher proportion of 2n cells, whereas OX cultures had a higher proportion of ≥4n cells than the WT (Figure 6b,c). In Pseudokirchneriella subcapitata , cells treated with the herbicide Metolachlor exhibit slower growth and accumulate multinucleate cells (Machado and Soares, 2020) similar to the MADS OX cultures. This phenotype results from disturbance of the reproductive cycle, where autospore release is inhibited without a disruption in nuclear division (Machado and Soares, 2020).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Cell cycle analysis to study the ploidy of the cultures revealed that WT cultures had a higher proportion of 2n cells, whereas OX cultures had a higher proportion of ≥4n cells than the WT (Figure 6b,c). In Pseudokirchneriella subcapitata , cells treated with the herbicide Metolachlor exhibit slower growth and accumulate multinucleate cells (Machado and Soares, 2020) similar to the MADS OX cultures. This phenotype results from disturbance of the reproductive cycle, where autospore release is inhibited without a disruption in nuclear division (Machado and Soares, 2020).…”
Section: Resultsmentioning
confidence: 97%
“…In Pseudokirchneriella subcapitata , cells treated with the herbicide Metolachlor exhibit slower growth and accumulate multinucleate cells (Machado and Soares, 2020) similar to the MADS OX cultures. This phenotype results from disturbance of the reproductive cycle, where autospore release is inhibited without a disruption in nuclear division (Machado and Soares, 2020). Overexpression of CsubMADS1 had a similar effect on C‐169 cells.…”
Section: Resultsmentioning
confidence: 97%
“…Under less stressful conditions, algal reproduction occurs via a two‐autospore mode, which is not accompanied by an increase in cell size. In the case of SMET, researchers found that the cells’ ability to split and perform the final stage of mitosis was being inhibited, which resulted in an increase in algal size (Machado & Soares, 2020, 2021). Changes in the reproductive mode and physiology in response to stress were seen in the alga Parachlorella kessleri after exposure to SMET (Maronić et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthetic performance of Photosystem II (PSII) of P. subcapitata, a good stress indicator, was evaluated by PAM fluorometry using a Junior PAM-fluorometer (Walz, Germany) as described by Machado and Soares (2020). PSII is the first complex protein that executes the initial reaction of photosynthesis.…”
Section: Photosynthetic Performancementioning
confidence: 99%